2016
DOI: 10.1089/vim.2015.0070
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Measles, Mumps, and Rubella Antibodies in College Students in Mumbai, India

Abstract: Measles, Mumps, and Rubella (MMR) are vaccine preventable viral infections, which cause significant mortality and morbidity globally. Increased incidence rates of these infectious diseases are observed in young adults. Information on seroprevalence data on MMR in India is limited. The objective of this study was to determine the prevalence of IgG antibodies against MMR among young adults. This was a descriptive cross-sectional study involving 192 healthy college students from Maharshi Dayanand College, Mumbai.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…13 These results are also in par with few studies conducted in adolescent and adult females in India. 14 However, it is higher when compared to many other studies with adolescents or adult females as study subjects. [15][16][17] Rates of rubella immunity have been variable in different parts of the world.…”
Section: Rubella Seropositivity Characteristicsmentioning
confidence: 78%
“…13 These results are also in par with few studies conducted in adolescent and adult females in India. 14 However, it is higher when compared to many other studies with adolescents or adult females as study subjects. [15][16][17] Rates of rubella immunity have been variable in different parts of the world.…”
Section: Rubella Seropositivity Characteristicsmentioning
confidence: 78%
“…Approximately 95% of those vaccinated have been found to have detectable measles antibodies 11 years after receiving the initial MMR vaccination and 15 years after receiving the second dose 23 . Another study on subjects in India between 18 and 23 years of age found rates of seropositivity of 79%, 91%, and 88% for measles, mumps, and rubella, respectively, as well as a higher overall seroprevalence among males 25 . In a study on subjects in the United States between 12 and 29 years of age, the rates of measles, mumps, and rubella seropositivity were found to be 92.0%, 87.6%, and 95.3%, respectively 26 .…”
Section: Discussionmentioning
confidence: 96%
“…The seronegativity to measles and mumps were 16.12% and 11.4%, respectively. Gohil et al 9 have earlier reported higher seronegativity to rubella-specific Recently, the European Centre for Disease Prevention and Control identified gaps in vaccination of teenagers and young adults as the surveillance data indicated that 80% of individuals of these age groups who contracted measles in 2017 were not vaccinated. 10 Seroprotection against measles is lower when vaccine is received at 9 months than at 12 months.…”
Section: Discussionmentioning
confidence: 99%